Explore the operational performance of phase change radiation terminal heating system in different heating zones of China - Zhang, Zhen; Yu, Xiaoqiang; Li, Jie; Wang, Lu; Jin, Bo; Niu, Getu; Yang, Zhengliang; Li, Chenxia (Frontiers in Energy Research, 2024)
Introduction Heating is one of the main factors leading to high energy consumption and serious carbon emissions in buildings. The clean heating system formed by the coupling of phase change building maintenance structure and solar heating system can improve the thermal storage density of the building maintenance structure, while reducing energy consumption in winter while maintaining a comfortable room temperature through stable energy security. Methods Therefore, a phase change radiation terminal heating (PCRTH) system with the phase change radiation module as the terminal and the solar energy and air energy as the clean heat source is established in this study. Nanjing, Tianjin and Shenyang in China were selected as the study zones which correspond to the hot summer and cold winter zone, the cold zone and the severe cold zone respectively. The operational effect of the PCRTH system in different climate zones was studied, and the parameters of the PCRTH system were optimized by the GenOpt program combined with Hooke-Jeeves optimization algorithm. Results The analysis results show that the cascade phase change radiation terminals in the three zones reduced room temperature fluctuation, energy consumption and carbon dioxide emissions, but the heating cost was higher. After the Hooke-Jeeves optimization algorithm was used to optimize the PCRTH system parameters in three zones, the PCRTH system heating cost was reduced, and the PCRTH system energy consumption and PCRTH system carbon dioxide emissions were further reduced. Discussion Therefore, the building heating system composed of PCM maintenance structure and renewable energy has great application advantages in maintaining a comfortable room temperature and improving heating system energy conservation and environmental protection.